Banana peels-derived shape-regulated nanocellulose for effective adsorption of Nile blue A dye - Patel, Dinesh K.; Won, So-Yeon; Han, Sung Soo (International journal of biological macromolecules, 2025)
Industrial wastes, including dyes and other chemicals, are significant sources of water pollution. The adsorption process is often explored in water purification. However, developing low-cost, sustainable adsorbents with good dye removal capacity remains challenging. We developed shape-regulated nanocellulose from waste banana peels through chemical treatment and examined their Nile blue A dye removal efficiency to address these limitations. The average diameter and length spherical (s-NC) and rod-shaped nanocellulose (CNCs) were 43.29 ± 5.97 and 137.61 ± 3.86, respectively. The zeta potential of the s-NC and CNCs was −34.5 ± 0.14 and − 27.6 ± 0.21 mV, respectively. The s-NC demonstrated improved thermal stability and cytocompatibility vis-à-vis CNCs. The s-NC exhibited enhanced dye removal potential compared to CNCs. Nearly 63.75 % and 87.32 % of dye were removed with 10 mg of CNCs and s-NC within 10 min of contact time, respectively. The adsorption isotherm was best fitted with Freundlich isotherm with a maximum adsorption capacity (qm) of 54.37 mg/g. Furthermore, the adsorbent demonstrated good recyclability and maintained ~68 % removal efficiency until six cycles. The adsorbent exhibited prolonged periods of stability under dye solution. These findings open a new direction in developing cost-effective and sustainable adsorbents/composite membranes by selecting suitable nanomaterial for water purification. [Display omitted] •The waste banana peels were successfully converted into value-added nanocellulose.•The extracted nanocellulose exhibited negatively charged surface (−34.5 ± 0.14 mV) characteristics.•The nanocellulose exhibited broad working conditions (temperature up to 60 °C, pH 2–12, and ion concentrations (up to 1 M).•Effectively removed 98.86 % of Nile blue A dye using 30 mg of nanocellulose in 10 min.•Maintained ~68.3 % dye adsorption efficiency after six cycles, showing good recyclability potential.